Distributed consensus control of nonlinear multi-agent systems with sensor uncertainty - Li, Hanfeng (2023)
This article focuses on the distributed consensus control problem for nonlinear multi-agent systems subject to sensor uncertainty. To be specific, we study nonlinear multi-agent systems of lower or upper triangular structure with unknown growth rate and sensor uncertainty. A new time-varying gain approach is proposed to construct observers as well as distributed output-feedback controllers. By selecting suitable design parameters, the leader-follower consensus of nonlinear multi-agent systems is achieved. Different from the existing results, a time-varying function in a logarithmic form is introduced to deal with unknown growth rate. Moreover, a monotonically increasing time-varying function is constructed to cope with uncertain sensor sensitivity. Two simulation examples are provided to demonstrate the effectiveness of the proposed distributed consensus control algorithms.